2010
DOI: 10.1136/vr.c4477
|View full text |Cite
|
Sign up to set email alerts
|

European field study of the efficacy and safety of the novel anthelmintic monepantel in sheep

Abstract: During 2007, a large-scale controlled, multicentre, blinded and randomised field study was conducted in Scotland, England and France to assess the efficacy and safety of monepantel, the first molecule to be developed from the recently discovered amino-acetonitrile derivatives class of anthelmintics, in sheep. Monepantel was administered orally, at a minimum dose of 2.5 mg/kg bodyweight, for the control of gastrointestinal nematodes in sheep maintained at pasture in a range of commercial production systems. Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Various studies in sheep have confirmed that monepantel is effective against adult and larval stages of all key GIN species including H. contortus, Teladorsagia spp., Trichostrongylus spp., and Nematodirus spp. Sager et al, 2009;Jones et al, 2010;Kaminsky et al, 2011). In llamas, however, the dose rate recommended for sheep was too low to reduce GIN faecal egg output efficiently (Dadak et al, 2013a).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Various studies in sheep have confirmed that monepantel is effective against adult and larval stages of all key GIN species including H. contortus, Teladorsagia spp., Trichostrongylus spp., and Nematodirus spp. Sager et al, 2009;Jones et al, 2010;Kaminsky et al, 2011). In llamas, however, the dose rate recommended for sheep was too low to reduce GIN faecal egg output efficiently (Dadak et al, 2013a).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…The second anthelmintic compound from another class is derquantel, which was introduced into the market in 2010 as Startect® (Pfizer Animal Health), a combination of derquantel and abamectin, a long-known ML. While the spectrum and efficacy of monepantel has been well documented (Hosking et al 2008, 2009a, b, 2010; Kaminsky et al 2009; Mason et al 2009; Sager et al 2009, 2010; Jones et al 2010), there is little information published on the spectrum of efficacy of derquantel (Little et al 2010). Of particular interest is the efficacy of these new compounds against ML-resistant nematodes.…”
Section: Introductionmentioning
confidence: 99%